(untitled) (Eduscotech, 2023)
This study aims to analyze the effect of traditional games on the development of gross motor skills in early childhood at TK Karangrejo Magetan. Conducted in September 2022, the research focused on evaluating the changes in children’s gross motor skills through various types of traditional games implemented in the school environment. A quantitative approach using a pretest-posttest experimental design was adopted. The sample consisted of 30 children aged 4-6 years from TK Karangrejo Magetan, divided into two groups: the experimental group that participated in traditional games and the control group that did not. Data were collected through direct observation of children’s motor skills before and after the participation in traditional games, and analyzed using t-tests to determine significant differences. The results showed a significant improvement in the development of gross motor skills, particularly in balance, coordination, and agility. This finding concludes that traditional games positively impact the development of gross motor skills in early childhood, making them an effective learning method to enhance children’s physical abilities at TK Karangrejo.